(NbORW)QÆJ (B:s)E (NROMAN(B-(NDRAMA (B/s - (NhORUNVIJ(B, (N`R)QÆJ mIHAJLOWI^(B,s)E ((NkI)QÇW (B:s)E (NrADQNSXKIJ PISXMENNIK(B,s, 1987)
(NrOMAN (B"(NbORW)QÆJ(B" (NPRISWQ^ENIJ VITT@ Æ TWOR^OSTÆ m(B.(Np(B. (NsTARICXKOGO(B, (NWIDATNOGO UKRAÇNSXKOGO PISXMENNIKA DRUGOÇ PORLOWINI hæh STOLÆTTQ(B, (NPOETA(B, (NDRAMOTURGA(B, (NPROZAÇKA(B, (NPEREKLADA^A(B, (NWIDAWCÆ(B, (NTEATRALXNOGO Æ GROMADSXKOGO DÆQ^A(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E